Control System for Watering and Lighting of Chrysanthemum Plants in IoT-Based Greenhouse - melani, meikeu; Aminah, Siti; Suryatini, Fitria (Emitor: Jurnal Teknik Elektro, 2025)
Indonesia is a rapidly developing horticultural country, with ornamental plants such as orchids and chrysanthemums contributing significantly to its horticultural economy. To improve the quality of these ornamental plants, an automatic control system is needed to regulate environmental parameters such as soil moisture and lighting. This study developed an automatic control system based on the Internet of Things (IoT) and fuzzy logic to monitor and manage lighting and soil moisture in a greenhouse according to the plant’s growth phase. The system utilizes an ESP32 microcontroller, a light sensor, and a soil moisture sensor, with data transmitted to the Firebase platform and displayed via an Android application built with Kodular. The test results show that the system performs well. The soil moisture sensor achieved an average accuracy of 82.33%, while the calibrated light sensor using linear regression reached an accuracy of 98.15%. The fuzzy logic control system on the microcontroller showed an average error of only 4.35% compared to MATLAB simulations, with a stable irrigation response (1 minute 12 seconds delay, 4 minutes 31 seconds rise time, and 6 minutes settling time without overshoot). The use of LED lighting significantly enhanced the vegetative growth of chrysanthemum plants. The Android application functioned optimally across all key features, and the communication system was successfully tested over a distance of more than 160 km without disruption. These findings demonstrate that the proposed system is effective for intelligent and efficient plant monitoring and management in a greenhouse environment.